Early Paradoxical Increase of Dopamine: A Neurochemical Study of Olfactory Bulb in Asymptomatic and Symptomatic MPTP Treated Monkeys - Pifl, Christian; Reither, Harald; del Rey, Natalia Lopez-Gonzalez; Cavada, Carmen; Obeso, Jose A.; Blesa, Javier (Frontiers in Neuroanatomy, 2017)
Parkinson’s disease (PD) is a neurodegenerative disease with both motor and non-motor manifestations. Hyposmia is one of the early non-motor symptoms, which can precede motor symptoms by several years. The relationship between hyposmia and PD remains elusive. Olfactory bulb (OB) pathology shows an increased number of olfactory dopaminergic cells, protein aggregates and dysfunction of neurotransmitter systems. In this study we examined tissue levels of dopamine (DA) and serotonin (5-hydroxytryptamine, 5-HT) and their metabolites, of noradrenaline (NA) and of the amino acid neurotransmitters aspartate, glutamate, taurine and γ-aminobutyric acid in OBs of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) treated Macaca fascicularis in different stages, including monkeys who were always asymptomatic, monkeys who recovered from mild parkinsonian signs, and monkeys with stable moderate or severe parkinsonism. DA was increased compared to controls, while neither NA and 5-HT nor the amino acid neurotransmitters were significantly changed. Furthermore, DA increased before stable motor deficits appear with +51% in asymptomatic and +96% in recovered monkeys. Unchanged DA metabolites suggest a special metabolic profile of the newly formed DA neurons. Significant correlation of homovanillic acid (HVA) with taurine single values within the four MPTP groups and of aspartate with taurine within the asymptomatic and recovered MPTP groups, but not within the controls suggest interactions in the OB between taurine and the DA system and taurine and the excitatory neurotransmitter triggered by MPTP. This first investigation of OB in various stages after MPTP administration suggests that the DA increase seems to be an early phenomenon, not requiring profound nigrostriatal neurodegeneration or PD symptoms.